Generic Medicines : Perceptions Of Physicians, Pharmacists, Consumers, Final Year Medical And Pharmacy Students In Iraq - Al-Sharrad, Adheed Khalid Sharrad (2011)
Generic medicines provide an opportunity for major savings in health care expenditure to both government and consumers Within this context, no studies have been conducted in Iraq regarding the perceptions held by physicians, pharmacists, consumers and future practitioners such as medical and pharmacy students towards the prescribing, substitution, and use of generic medicines Therefore, the aims of this thesis were to investigate perceptions and knowledge held by both the healthcare providers and consumers toward the quality use of generic medicines in Iraq. In order to reach these aims, qualitative methods were used. Ten physicians were interviewed. Thematic content analysis of the interviews identified seven major themes: medicine prescribing practices, knowledge of therapeutic equivalency of generic medicines, patients’ acceptance of generic medicines, counterfeit medicines, source of information on medicines and the influence of drug advertising on the choice of medicine, brand substitution practices by community pharmacists, and strategies to improve the usefulness of generic medicines. A total of ten pharmacists were also interviewed. Five major themes emerged: generic medicines substitution practices, knowledge about generic medication, quality and safety of generic medicines, patient education by pharmacists regarding generic medicines and strategies to improve generic medicine utility.